Pengabdian Kepada Masyarakat tentang Penyuluhan Kesehatan Mulut dan Menjaga Gigi yang Baik dan Benar di Desa Kronjo, Kabupaten Tangerang Provinsi Banten - Ganjar Sidik Gandara; Dedy Khaerudin; Irma Nurmala Dewi; Sika Noviani; Afri Handayani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Maintaining body health is an obligation for each of us. The most crucial body health from our five senses that must be maintained is oral health, which includes the teeth and gums because teeth are a part of the body that serves a purpose in chewing food. Bina Bangsa University students share their knowledge through this community service in the health sector. Children at SDN 3 Kronjo are the target audience for this PKM, which aims to address a variety of dental health issues that they may encounter. Maintaining oral hygiene is the most important preventive measure for infections that can lead to cavities. The solution to this program is to plan material delivery and how to overcome the health issue of cavities, which frequently occurs in elementary school children. The activity takes the form of health education provided by Bina Bangsa University (UNIBA) students to participants, who are elementary school children in classes 5 and 6. Meanwhile, UNIBA KKM Implementers carry out the extension method continuously throughout the KKM program, as programmed. This KKM activity also includes practice on how to brush your teeth properly and the consequences of not maintaining healthy teeth, gums, and oral cavities.